The Influence of Climate Change Considerations on Energy Policy: The Case of Russia - Anil Markandya; Alexander Golub; E. Strukova (Fondazione Eni Enrico Mattei (FEEM), 2003)
To those working on climate change it is obvious that energy policy should be influenced by climate change considerations. The question that this paper seeks to answer is, to what extent do they influence policy and what contribution can a careful analysis of the costs and benefits of climate change options have on the formulation of that policy. We seek to understand this by looking in some detail at energy policy formulation in Russia. To do so it is necessary to look at the whole set of issues that determine energy policy. These include energy security, macroeconomic and uncertainty factors, local environmental issues and social issues. The analysis has been carried out for a specific case that of the RF, where energy policy is currently under formulation to 2010. Two options have been looked at: a High Coal option, where there would be a substantial change in fuel mix away from gas to coal; and a High Gas option where the current fuel mix is retained and the increase in demand is met from all sources in proportion to current use. The analysis shows that, at international prices for fuels, the High Coal option is attractive. However, when we include the potential decline of price for natural gas in the European market, the relative preference for this option drops dramatically but it still remains the preferred option. When, account is also taken of the carbon benefits of the High Gas option, using plausible values for carbon, the attraction of the High Coal option is further reduced but not altered. When finally account is taken of the health associated with the lower use of coal in the High Gas option, the preference can be reversed but it requires a critical value for the health benefits. This critical value at around 3,000 for a life year lost – is plausible for the RF, if anything the actual value is probably higher. What the analysis shows is the need for a careful evaluation of the different factors determining energy policy. Among these is climate change. It is not the critical factor but it can be an important one. Perhaps more important are the environmental benefits that go with the lower carbon High Gas options.
Keywords: H41; Q28; Q32; D62; J60; 330; Climate policy; Russia; Ancillary benefits; Klimawandel; Energiepolitik; Russland